Goals for teaching: Towards a framework for examining motivation of graduating teachers - Mansfield, C.; Wosnitza, M.; Beltman, Susan (University of Newcastle, 2012)
Teacher motivation is an important field of research, especially in countries where teacher retention and quality have become prominent concerns. This paper presents a conceptual framework for understanding the stage appropriate goals for teaching of graduating teacher education students. Generated from empirical data and grounded in established literature (Ford, 1992; Ford & Nichols, 1987) the framework shows that both within-person and person-environment consequences inform goals for teaching. This framework makes a unique contribution to the field of teacher motivation, providing a tool to explore the content of teachers’ goals, thus providing further insights into teacher motivation.